Hatred: understanding our most dangerous emotion - Brogaard, Berit (Oxford University Press, 2020)
"Hatred: Understanding Our Most Dangerous Emotion The first in-depth philosophical analysis of personal hate and group hate, Hate: Understanding Our Most Dangerous Emotion explores how personal hatred can foster domestic violence and emotional abuse, how hate-proneness is a main contributor to the aggressive tendencies of borderlines, narcissists and psychopaths, how seemingly ordinary people embark on some of history's worst hate crimes, and how cohesive groups, subjected to spontaneous forces of group polarization, can develop extremist viewpoints of the sort that motivate hate crimes, mass shootings, and terrorism. The book's first part explores hate in intimate relationships, looking for an answer to the question of why our intimate relationships can survive hate and resentment, but not disrespect or contempt. Berit "Brit" Brogaard shows that where contempt creates an irreparable power imbalance, hate is tied to fear, which our brains may reinterpret as thrill, attraction and excitement. But this can also make hate a dangerous emotion that convinces people to hang onto abusive relationships. When tied to vengeance and the dark triad of personality, hate is not only dangerous but also dehumanizing. Vengeance and the dark personalities are not essential to hate, however. Without them, hate can have more admirable ends. The book's second part explores the polarizing forces that can bias cohesive groups of like-minded individuals and contribute to what is effectively a hate crisis. Drawing on history, politics, legal theory, philosophy, and psychology, Brogaard shows how cultural myths about femininity, ethnic groups, and the land of opportunity perpetuate misogyny, white supremacy and anti-Semitism. But, she argues, politicians and policymakers have it in their power to address the hate crisis through legislation that preserves the original incentive behind the first-amendment right to free speech"--